Pterostilbene, An Active Constituent of Blueberries, Suppresses Proliferation Potential of Human Cholangiocarcinoma via Enhancing the Autophagic Flux - Wang, Dong; Guo, Haoran; Yang, Huahong; Wang, Dongyin; Gao, Pujun; Wei, Wei (Frontiers in Pharmacology, 2019)
Background: Human cholangiocarcinoma (CCA) is a highly lethal cancer that occurs in the biliary tract. It is characterized by early invasion, poor outcomes, and resistance to current chemotherapies. To date, an effective therapeutic strategy for this devastating and deadly disease is lacking. Pterostilbene, a natural compound found in extracts of many plants, including blueberries, kino tree, or dragon blood tree, has several health benefits. However, its effects on CCA have not been well clarified. Here, we investigated the potential application of pterostilbene in the treatment of human CCA in vitro and in vivo. Methods: The effects of pterostilbene on CCA cells were determined by assessing cell viability (CCK), cell proliferation, and colony formation. Cell cycle arrest and apoptosis were measured by flow cytometric analysis, whereas proteins related to cell autophagy were detected by immunofluorescence and immunoblotting assays. A well-established xenograft mouse model was used to evaluate the effects of pterostilbene on tumor growth in vivo. Results: Pterostilbene induced dose-dependent and time-dependent cytotoxicity, inhibited proliferation and colony formation, and caused S phase cell cycle arrest in CCA cells. Instead of triggering apoptotic cell death in CCA cells, pterostilbene was found to exert potent autophagy-inducing effects in these cells, and this correlated with p62 downregulation, elevated expression of endogenous Beclin-1, ATG5, and LC3-II, and increase in LC3 punctate levels. Pretreating cancer cells with the autophagy inhibitor, 3-MA, impaired autophagy enhancement and antitumor activity caused by pterostilbene. Finally, we confirmed that pterostilbene inhibited tumor growth in the CCA xenograft mouse model with minimal general toxicity. Conclusion: Taken together, our findings indicate that pterostilbene, through autophagic flux induction, acts as an anti-cancer agent in CCA cells.